A Review of Hyperspectral Imaging for Chicken Meat Safety and Quality Evaluation: Application, Hardware, and Software. Issue 2 (22nd February 2019) - Fu, Xiaping; Chen, Jinchao
Abstract: Food quality and safety issues have received widespread attention around the world. Traditional analytical methods are cumbersome, time consuming, and disruptive. Consumers and businesses are in desperate need of a fast, nondestructive test to evaluate the safety and quality of food. Chicken is an important food source for the human diet and has a high consumption rate. Its quality and safety issues are especially important. The hyperspectral imaging (HSI) technique combines the main characteristics of the spectroscopy technique and the imaging technique to achieve fast, nondestructive testing and demonstrates great potential for evaluating the food safety and quality of chicken. For the past few years, there have been many studies on the HSI technique for the detection and evaluation of chicken meat safety and quality. Therefore, the purpose of this article is to provide a detailed overview of the HSI technique for microbiological safety detection and quality attribute assessments of chicken meat. In addition, the hardware and software used in the HSI systems are also summarized and compared. Finally, some opinions on the focus of future research and its applications in the modern poultry industry are presented.